Uncovering the economic value of natural enemies and true costs of chemical insecticides to cotton farmers in China - Huang, Jikun; Zhou, Ke; Zhang, Wei; Deng, Xiangzheng; Werf, Wopke van der; Lu, Yanhui; Wu, Kongming; Rosegrant, Mark W. (IOP Publishing, 2018)
Little empirical evidence on economic value of biological control of pests at farm level is available to improve economic decision-making by farmers and policy makers. Using insect sampling and household survey in an integrated bio-economic analysis framework, this paper studies farmers' crop management practices in cotton in the North China Plain, and estimates the marginal value of natural enemies and costs of chemical insecticides to farmers. Ladybeetles (mainly Harmonia axyridis, Propylea japonica, and Coccinella septempunctata), the dominant natural enemy group that controls the primary pest (aphid) in cotton in our study area, provide a significant economic benefit that is unknown to the farmers. Even at the current high levels of insecticide use, additional ladybeetle provides an economic benefit of 0.05 CNY (USD 0.01) to farmers. The use of broad-spectrum insecticides by farmers is alarmingly excessive, not only undermining farmers' profitability but also inducing social costs as well as disruption of the natural pest suppression system. Doubling current ladybeetle density in cotton field could gain an estimated USD 300 million for cotton farmers in China, providing a strong economic case for policies to move the pest control system toward a more ecologically-based regime, with positive consequences for farm income and environmental health. With rising use of biological control service provided by natural enemies in cotton fields, significant falls in farmers' insecticide use would be expected, which could raise the value of ladybeetles and other natural enemies even further. The results indicate that there is an urgent need to rationalize inputs and move forward to improved agro-ecosystem management in smallholder farming system. Raising knowledge and awareness on the costs and value of biological pest control versus insecticides among farmers and policy makers and having effective extension service are priorities toward achieving a more ecologically-based approach to crop protection on smallholder farms.